Epidemiology of Pediatric Nonballistic Firearm Injuries to the Upper Extremity in the United States From 2000 to 2017. (March 2022) - Summers, Andrew R.; Cheema, Adnan N.; Pirruccio, Kevin; Kazmers, Nikolas H.; Gray, Benjamin L.
Background: This study aimed to describe the epidemiology of pediatric upper extremity injury secondary to nonballistic firearms in the United States.Methods: The National Electronic Injury Surveillance Survey (NEISS) database was queried between 2000 and 2017 for injuries to the upper extremity from nonballistic firearms in patients aged ≤18 years. In total, 1502 unique cases were identified. Using input parameters intrinsic to the NEISS database, national weighted estimates were derived using Stata/IC 15.1 statistical software (StataCorp LLC, College Station, Texas), which yielded an estimate of 52 118 cases of nonballistic firearm trauma to the upper extremity who presented to US emergency departments over the study period. Descriptive statistics were performed using NEISS parameters.Results: An average of 2895 annual pediatric upper extremity nonballistic firearm injuries were identified between 2000 and 2017. Over 91% were sustained by men, and adolescents aged 12 to 18 were the most commonly injured (69.8%). Only 3.5% of all injuries required inpatient admission, and the most common sites of injury were the hand (41.1%), followed by fingers (35.9%).Conclusions: We conclude that nonballistic firearm injuries represent a significant burden of disease to adolescent men in the United States.